Assessment-centered teaching : a reflective practice - 4 0 16; DiRanna, Kathryn; 5 (Thousand Oaks, CA : Corwin Press :;WestED, 2008)
Discusses strategies for educators adjust their teaching methods to balance assessment along with instruction, which will enable teachers to discover learning gaps and improve student comprehension of complex subject matter. Includes a CD-ROM.
Includes bibliographical references (p. 197-200) and index.
Professional;Professional
System requirements not stated.
Keywords: 2 -- 0; 6; Evaluation. -- Teaching;Effective teaching.;Reflective teaching.;Teaching.; 20; 2